The wintertime brown adipose tissue thermogenesis of New York City residents amidst climate change - Stephanie B. Levy; Shelby Pirtle; Ruthbernick Bastien; Kandra Cruz; Jahnae Vernon (Annals of Human Biology)
Background The built environment buffers residents of large cities, such as New York (NYC), from exposure to low temperatures. Furthermore, average winter temperatures are rising in NYC due to climate change. The degree to which NYC residents exhibit metabolic adaptations to cold stress is currently unclear.Aim This study quantified variation in brown adipose tissue (BAT), energy expenditure (EE), and ambient temperature among NYC residents.Subjects and methods We recruited 46 adults (31 females; 15 males) and quantified anthropometrics, change in EE, and BAT thermogenesis after a cooling condition in the lab. A subsample of 21 participants wore temperature loggers for three days in order to quantify ambient temperature exposure.Results BAT thermogenesis was not significantly associated with change in EE. Participants that were exposed to lower average temperatures exhibited greater BAT thermogenesis (p = 0.013). Change in EE, however, was not significantly associated with time spent outside nor average temperature exposure.Conclusion Our study provides mixed evidence for the role of BAT thermogenesis in metabolic adaptations to cold stress among NYC residents. Many young adults in NYC are exposed to minimal amounts of cold stress, and this trend is likely to be exacerbated by climate change.